Redaction team's strategy of Lensa Manakarra program at PT Manakarra TV West Sulawesi in improving the quality of news production. - Mukrimah, Mukrimah; Tajibu, Kamaluddin (Jurnal Mercusuar, 2020)
This research discusses the Editorial Team Strategy of Lensa Manakarra Program at PT. Manakarra TV West Sulawesi in Improving News Production Quality. The research aims to (1) identify the obstacles in the production process of the Lensa Manakarra program, and (2) determine the strategies and presentations of the Manakarra TV editorial team on the Lensa Manakarra program in improving the quality of news production.